Control the deposition uniformity using ring cathode by DC discharge technique - Aadim, Kadhim A. (Iraqi Journal of Physics, 2019)
Simulation of direct current (DC) discharge plasma using COMSOL Multiphysics software were used to study the uniformity of deposition on anode from DC discharge sputtering using ring and disc cathodes, then applied it experimentally to make comparison between film thickness distribution with simulation results. Both simulation and experimental results shows that the deposition using copper ring cathode is more uniformity than disc cathode